A New Necessity : First Tyne International 1990. - Pohlen, Annelie; First Tyne International, Newcastle upon tyne, 1990 (Newcastle upon Tyne : Tyne International, 1990)
Adams, Dennis ; Alexander, Keith ; Araeen, Rasheed ; Atkinson, Sue ; Atkinson, Terry ; Furlong, William ; Baker Woodhouse, Helen ; Balkenhol, Stephan ; Bewley, Jon ; Bradley, Paul ; Cadieux, Geneviève ; Christo ; Coleman, James ; Constant, Christine ; Culbert, Bill ; Ferrara, Jackie ; Finn-Kelcey, Rose ; Goard, David ; Graham, Dan ; Horrigan, Jefford ; Jaffe, Lee ; Kawamata ; Lawson, Thomas ; Mullican, Matt ; Muntadas ; Newling, John ; Ohtake, Shinro ; Ormsby, Barrie ; Richter, Gerhard ; etc.
A New Necessity : First Tyne International 1990, Newcastle upon Tyne, 1990
boek